G03 Visuomotor integration deficits in premanifest and early manifest Huntington's disease in the TRACK-HD study. (16th November 2010) - Say, M J; Jones, R; Scahill, R I; Dumas, E M; Coleman, A J; dar Santos, R; Justo, D; Campbell, C; Queller, S; Tabrizi, S J; Stout, J C
Abstract : Background/aims: Visuomotor integration deficits have been documented in manifest Huntington's disease, with disproportionate impairments when indirect visual cues are relied upon. Visuomotor integration in premanifest gene expansion carriers has not been studied under such conditions. Methods: 239 gene expansion carriers spanning over a decade before predicted onset until early stage disease and 122 control subjects were administered a circle tracing task. Performance was guided by direct or indirect visual cues. Outcome measures targeted accuracy, speed and speed of error detection and correction. Predictor variables included disease group and disease burden (age×(CAG−35.5)). Correlations with 3T MRI voxel based morphometry of grey and white matter volume reduction were computed. Results: Increased HD disease burden was associated with reduced accuracy and slowed performance in both direct and indirect circle tracing conditions. Expansion carriers who were more than a decade before predicted clinical onset showed deficits in performance compared with controls. Comparing performance in the indirect with the direct condition, expansion carriers had a disproportionate increase in errors than controls. Expansion carriers showed greater latencies in detecting an error when heading away from target, and in correcting an error when heading back to target. Slowed performance in the indirect circle tracing condition was associated with grey matter volume reduction within the left somatosensory cortex in voxel based morphometry analyses. Conclusions: Visuomotor integration deficits appear in expansion carriers many years before onset with the use of indirect visual cues especially appearing to impact adversely on accuracy. Slowed performance under indirect visual cues appears to be associated with atrophy of the left hemisphere somatosensory cortex, which likely reflects the proprioceptive demands of the task.